UMMIBOT sebagai Media Layanan Informasi Penerimaan Mahasiswa Baru Universitas Muhammadiyah Sukabumi - M. Rizky Suherlan; Asriyanik; Agung Pambudi (Jurnal Informatika Terpadu, 2023)
The continuous advancement in information and communication technology has overcome geographical limitations and enhanced the speed of information and knowledge transfer. Information and communication technology has been applied in various aspects, including improving services, speeding up communication processes, facilitating access to information, and effectively sharing information. One significant technological innovation is the chatbot, an artificial intelligence technology that enables interactive communication. Implementing a chatbot at the Admissions Office of Muhammadiyah University Sukabumi (UMMI) aims to assist prospective students in obtaining information regarding new student admissions. The main challenge addressed is the limitation of office hours, which often hinders prospective applicants from accessing information quickly. This research employs the Natural Language Processing (NLP) method in chatbot development, intending to enable the chatbot to understand natural language and search for relevant information. The research objective is to create an efficient chatbot to respond to user inquiries outside of office hours. The stages of chatbot development using the NLP method encompass data collection, text processing, feature engineering, modeling, inference, deployment, and evaluation. The research results indicate that the chatbot, named UMMIBOT, successfully achieved a functional accuracy rate of 83.67%, addressing the issue of office hour limitations and providing responses that align with user input with high accuracy.